Unusual Cases of the Transmigrated Mandibular Canines: Report of 4 Cases - Aktan, Ali Murat; Kara, Sami; Akgunlu, Faruk; sman, Eren; Malkoc, Siddik (European Journal of Dentistry, 2008)
The canine impaction is not uncommon in dental literature, but the transmigration of mandibular canine is a rare phenomenon, and some of them are far more extreme than others. In this study, we aimed to present the more extreme cases of the four transmigrated mandibular canine cases with special emphasis on their classification. (Eur J Dent 2008;2:122-126)
Keywords: Impaction; Transmigration; Canine; Panoramic radiograph